Analysis of Information Security Awareness Against Social Engineering Attacks - Fariz Fakhrul Arifin; Puspanda Hatta; Endar Suprih Wihidayat (Informatics Education Department, Faculty of Teacher Training and Education, Universitas Sebelas Maret, 2024)
Social engineering is a significant threat to information security, where attackers manipulate users to obtain highly confidential information. These attacks can target anyone, but people who are less vigilant are especially vulnerable. In a campus environment, it is crucial that students, who will soon enter the workforce, fully understand the dangers of social engineering and the potential impact on their future employers. This study aims to determine the level of information security awareness at the V campus of UNS Pabelan, with a focus on FKIP-PTIK students from the 2019-2020 classes. The research employed quota sampling, a technique for selecting a sample from a population based on specific characteristics until a desired size is reached. Using a Google Form questionnaire to collect primary and secondary data, the study analyzed the information with a quantitative descriptive approach. The results found that key indicators—including awareness, attitude, knowledge, and behaviors related to information security against social engineering attacks—were all in a